Pelatihan Literasi Keuangan Usaha: Analisis Trend Penjualan sebagai Upaya Peningkatan Potensi Pendapatan Usaha - Martdian Ratna Sari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The main problem of the business group is that business actors never record every order that occurs so that business actors are unable to calculate the profit of each sale specifically. The purpose of this business group service and empowerment program is to increase the potential for business income through trend analysis and sales projections. This service and empowerment program begins with analyzing needs and problems through interview and observation methods, then the business group as business actors is given training related to business financial literacy, training to analyze sales trends in the last 3 months, projecting potential income for the next 1 month, and detailed recording of each sales order. The results obtained are an increase in the knowledge and skills of business group members related to business finance, increased sales and orders by implementing profitable and unprofitable customer selection, and more detailed sales recording. Training and assistance in managing business finances are expected to make it easier for business groups to book sales orders every day and to make it easier for business groups to develop profitable business partners. The results of the evaluation of the implementation of the training program can be seen from the increase in income by 45%.